2008
DOI: 10.3201/eid1406.080029
|View full text |Cite
|
Sign up to set email alerts
|

Persistence ofYersinia pestisin Soil Under Natural Conditions

Abstract: As part of a fatal human plague case investigation, we showed that the plague bacterium, Yersinia pestis, can survive for at least 24 days in contaminated soil under natural conditions. These results have implications for defi ning plague foci, persistence, transmission, and bioremediation after a natural or intentional exposure to Y. pestis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 9 publications
2
105
0
Order By: Relevance
“…Some literature indicates that plague persistence in natural foci has a root cause in soils (Breneva et al, 2006;Eisen et al, 2008). This indication has been supported by the evidence that Y. pestis can survive in natural soil conditions from 24 days to 40 weeks (Ayyadurai et al, 2008).…”
Section: Introductionsupporting
confidence: 65%
“…Some literature indicates that plague persistence in natural foci has a root cause in soils (Breneva et al, 2006;Eisen et al, 2008). This indication has been supported by the evidence that Y. pestis can survive in natural soil conditions from 24 days to 40 weeks (Ayyadurai et al, 2008).…”
Section: Introductionsupporting
confidence: 65%
“…[9][10][11][12][13][14][15] Plague bacteria also may survive outside living hosts on carcasses or in the soil, but only limited evidence exists to suggest that such mechanisms are important for long-term survival in nature. 9,16,17 Plague likely evolved in Asia, 9,18,19 and has since spread broadly by various means, 18 including the transport of infected hosts and fleas along overland trade routes or aboard rat-infested ships during the three historically documented pandemics. The third of these pandemics and that most relevant to this study introduced plague to North American ports in the late nineteenth century; where it afterwards "escaped" into native rodent populations, eventually spreading east through the Rocky Mountains to the western edge of the Great Plains.…”
Section: Introductionmentioning
confidence: 99%
“…Low overall rates of plague exposure during and preceding epizootics among rodent (Stapp et al 2008) and nonrodent (Brinkerhoff et al 2009) mammalian species point to a nonmammalian source of Y. pestis infection to prairie dogs. Recent demonstrations of Y. pestis persistence in soils (Ayyadurai et al 2008, Eisen et al 2008b indicate that a mammalian reservoir may not be required for epizootic initiation, although it has not been demonstrated that soils contaminated with Y. pestis can initiate epizootic events in prairie dogs.…”
Section: Discussionmentioning
confidence: 99%